Analysis of meteorological effects of cosmic ray neutron component based on data from mid-latitude stations - Kobelev P. G.; Hamraev Y. B.; Yanke V. G. (Solar-Terrestrial Physics)
Precision neutron monitors providing continuous monitoring with a statistical accuracy of ~0.15 %/hr are effective for studying cosmic ray variations; therefore, contributions from other error sources should not exceed the contribution of this statistical error. Such possible sources primarily include changes in atmospheric pressure and humidity. The aim of the work is to estimate the barometric effect of the neutron component of cosmic rays for the low-latitude stations Tashkent and Alma-Ata (mountain), including periods of maximum solar activity. The technique developed on the basis of multifactor correlation analysis is applicable to processing data from any detectors of the worldwide network of neutron monitors. As a result, we have obtained annual average barometric coefficients of the neutron component at the stations Tashkent and Alma-Ata. The humidity effect was also estimated for the mid-latitude station Moscow. The study draws the conclusion that the approach considered can effectively solve the problem.